Contribution of students' perspective towards successful learning of Mathematics in English: a study in SMKA Tok Jiring, Kuala Terengganu / Zaliha Abdullah - Abdullah, Zaliha (2006)
The development of science and technology in Malaysia contributes to the success of Vision 2020 to become a reality. Part of this is the implementation of English in teaching mathematics which started in the year 2003. This research was done in view of the public outcry that students will face difficulties when they switch from Bahasa Melayu to English Language. It was conducted in Sekolah Menengah Kebangsaan Agama Tok Jiring, a school on the outskirts of Kuala Terengganu on 60 PMR students and 5 mathematics teachers. Questionnaires and interviews were used as instruments. From the study, it was found that the students of SMKATJ did quite well in their PMR Mathematics 2005 with the help of their teachers. It is hoped that this research on learning mathematics in English will convey positive attitude to students and teachers in the future.